2007
DOI: 10.1002/ange.200700543
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth and Lead Hanging‐Carboxylate Porphyrins: An Unexpected Homobimetallic Lead(II) Complex

Abstract: Eingefangen: Das Einfügen von PbII in ein Porphyrin mit 5,15‐Brücken mit angehängter Carboxylatgruppe ergab den ersten Homodimetallporphyrin‐Komplex eines zweiwertigen Metallions, der in Buchlers Klassifikation von Metalloporphyrinen als Klasse III/Typ M zu bezeichnen ist (siehe Bild). Da der Ligand auch leicht an das isoelektronische BiIII‐Ion koordiniert, könnte er als Chelator für 212Pb/212Bi‐Isotopenerzeuger fungieren.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Treatment of 4 with BBr 3 afforded porphyrin 1 while avoiding any decarboxylation reaction. As previously reported, in the distal strap of 1 , the carboxylic groups may be directed either toward or pointing away from the porphyrin plane. Therefore, heme model 1 has been designed to probe the influence of an apical carboxylic group on dioxygen affinity.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…Treatment of 4 with BBr 3 afforded porphyrin 1 while avoiding any decarboxylation reaction. As previously reported, in the distal strap of 1 , the carboxylic groups may be directed either toward or pointing away from the porphyrin plane. Therefore, heme model 1 has been designed to probe the influence of an apical carboxylic group on dioxygen affinity.…”
supporting
confidence: 58%
“…A second application of this synthetic strategy is represented by the facile synthesis of bifunctional chelates for the vectorization of α-emitter radionuclides. Indeed, it has been shown that a symmetrical bis-strapped porphyrin with the same type of malonate strap as 1 is able to coordinate a large cation such as bismuth(III), leading to a neutral complex . In such a complex, the carboxylate group of one strap coordinates to porphyrin-bound bismuth.…”
mentioning
confidence: 99%
“…This conformational flexibility has already been confirmed by X-ray crystallography in the coordination of large cations by this type of ligand, whether in the ααββ 27 or in the αβαβ conformation. 28 In the latter, it should be noted that an additional possible rotation of the strap comes from its hinges which are located at opposing meso positions denoted by the blue spheres in Figure 1. In other words, in model 2b, the carboxylic acid groups can only change their orientation from outside to inside the cavity by rotation around the benzylic groups but at an invariable distance from the iron atom imposed by rotation of the strap around the 5,15 meso-position axis.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The structure reveals a dinuclear complex with a mercury ion located on each side of the macrocycle. In contrast to the dinuclear lead complex of 1 ,8 1⋅Hg 2 lacks the C 2 symmetry, and the two metal ions sit in two different environments. The two sides of the porphyrin mainly differ by 1) the conformation of the two straps, the strap {Hg1} being more twisted than the strap {Hg2} (Figure 1 b, c), and 2) the out‐of‐plane positions of Hg1 and Hg2, which are located 1.733 and 1.408 Å from the 24‐atom mean plane, respectively.…”
Section: Methodsmentioning
confidence: 98%
“…In this context, the design of new porphyrin ligands with purposely introduced coordinating groups deserves particular attention. We recently reported a centrosymmetrical homo‐dinuclear complex of lead(II) with the L 4− ditopic ligand 1 (Scheme ) 8. We reasoned that, in the case of mercury(II), such a bis‐strapped chelate with hanging COOH groups could provide a means to obtain discrete species, rather than sandwich assemblies, and better control of the nuclearity.…”
Section: Methodsmentioning
confidence: 99%